Shanghai Cooperation Organization (Eurasian Journal of Learning and Academic Teaching, 2023)
The purpose of this article is to investigate the geopolitical situation in Central Asia; to study various approaches to strengthening the security of the region; to assess the growing role of the SCO in ensuring the security of Central Asian states; to trace the development of the foreign policy of regional actors; to study modern interethnic relations affecting security issues; to determine the role of state and non-state actors in these processes